The effect of surface treatment and thermal aging on the bonding of clear aligner attachments to provisional resin-based material: shear bond strength analysis - Shahin, Suliman Y.; AlQahtani, Norah; Abushowmi, Tahani H.; Siddiqui, Intisar A.; Akhtar, Sultan; Nassar, Essam A.; Gad, Mohammed M. (Frontiers in Oral Health, 2024)
ObjectivesThe aim of this study is to evaluate the effect of different surface treatments on the shear bond strength (SBS) of clear aligner attachments bonded to Bis-acryl provisional crowns.Methods120 cylindrical bisacrylic composite material (ProTemp type) specimens were prepared and divided into six groups (n = 20) based on surface treatment, control: (no treatment); super coarse grit diamond bur, carbide bur, alumina-blasting, non-thermal plasma treatment, and Er:YAG laser treatment. The features of treated surfaces were examined using scanning electron microscopy (SEM). A flowable composite resin (Transbond XT; 3M Unitek) was bonded to the specimens forming the attachment. Half of specimens were subjected to thermal cycling (5,000 cycles). SBS was measured before and after thermal cycling. Each specimen was loaded at the attachment/resin interface at a speed of 0.5 mm/min until failure. The nature of the failure was analyzed using the composite remnants index (CRI). Two-way ANOVA and Tukey HSD were used for data analysis α =  0.5. For CRI scores analysis, Kruskal-Wallis test and Dunn's multiple comparison were used as post-hoc test.ResultsSEM analysis showed that all surface treatments altered surface properties and increase surface bonding area. The specimens treated with plasma, Er:YAG laser, and alumina-blasting had higher SBS values before and after thermal cycling. In comparison to control plasma, Er:YAG laser, and alumina-blasting showed a significant increase in SBS (P < 0.001) while carbide and diamond bur groups showed no significant differences (P > 0.05). Thermal cycling significantly decreased the SBS of control, carbide bur, diamond bur, and Er:YAG laser while no significant effect of alumina-blasting and plasma group. Er:YAG laser and plasma groups significantly exhibited more dominance for scores 2 and score 3 and the absence of score 0.ConclusionAlumina-blasting, Er:YAG laser, or non-thermal plasma surface treatments increased the shear bond strength between clear aligner attachments and resin-based restorations.